A three-phase four-wire unified power quality conditioner without series transformers - Monteiro, L. F. C. (2012)
This work presents a topology for a Unified Power Quality Conditioner (UPQC), without series transformers, connected to a three-phase four-wire electrical grid. Based on the proposed power topology, the UPQC is able to compensate unbalanced-and harmonic-components, power factor and short-duration voltage variations (voltage sag/swell). In other words this UPQC consists in a universal solution capable to mitigate most power quality problems in an electrical installation. The applied control algorithms are based on instantaneous power definitions (active and non-active currents), together with a robust synchronizing circuit (PLL), to detect the phase angle of the fundamental positive-sequence component of the system voltage. A trustworthy model of the proposed UPQC was investigated in order to verify its performance under power quality problems observed at the load currents and system voltages.